Dopisy před odjezdem do ghetta Terezín - Bittnerová, Dana (Lidé města, 2005)
The aim of this minor contribution is to expand the known and available source basis related to the Holocaust by documents reflecting feelings of a participant prior to departure to the Ghetto. It presents three letters in Czech written between January and February of 1945 by Ms. Anna, 45. Ms. Anna was of Jewish origin and was married to a Catholic. The first letter talks of her preparations and at the same time it expresses hope that the transport will not eventually take place. The second one reflects skepticism of Ms. Anna who already received the order to report for the transport. The last letter was written at the assembly point. These three letters constitute quite unique material. They relate to us an insight to thinking of people being deported. They unequivocally reflect absurdity of that era projected into absurd behavior of the participants. The letters combine, on one hand, an attempt to maintain continuity of everyday family life even following deportation of family members to a Ghetto or to labor camps. On the other hand, these letters are filled with contemplation about preservation of personal dignity vis-a-vie the inhuman treatment rendered by their captors. The three letters of Ms. Anna are thus a testimony to what people slated for deportation thought, how they confronted their own system of values with the current realities and how they oriented themselves in new life-conditions and adapted to them.